2001
DOI: 10.1038/90074
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of secreted and transmembrane proteins critical to mouse development

Abstract: We describe the successful application of a modified gene-trap approach, the secretory trap, to systematically analyze the functions in vivo of large numbers of genes encoding secreted and membrane proteins. Secretory-trap insertions in embryonic stem cells can be transmitted to the germ line of mice with high efficiency and effectively mutate the target gene. Of 60 insertions analyzed in mice, one-third cause recessive lethal phenotypes affecting various stages of embryonic and postnatal development. Thus, se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
341
1
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 380 publications
(356 citation statements)
references
References 53 publications
10
341
1
3
Order By: Relevance
“…The trapped genes were distributed on all chromosomes except the Y, suggesting that a large number of genes across the genome could be accessed by this vector. Some loci seem to be more readily trapped than others, as also found by other large-scale gene trapping efforts using different vectors [19][20][21][22] , and 40 genes were trapped more than once. This phenomenon may be due to recombination hot spots, more permissive integration sites available in larger genes or a limited pool of genes that could be trapped in the genome.…”
Section: Cloning and Analysis Of Trapped Transcriptssupporting
confidence: 68%
See 1 more Smart Citation
“…The trapped genes were distributed on all chromosomes except the Y, suggesting that a large number of genes across the genome could be accessed by this vector. Some loci seem to be more readily trapped than others, as also found by other large-scale gene trapping efforts using different vectors [19][20][21][22] , and 40 genes were trapped more than once. This phenomenon may be due to recombination hot spots, more permissive integration sites available in larger genes or a limited pool of genes that could be trapped in the genome.…”
Section: Cloning and Analysis Of Trapped Transcriptssupporting
confidence: 68%
“…But all these screens are confined to ES cells or their differentiated derivatives and rely on reporter expression. Sequence-driven screens based on the identity of trapped genes [19][20][21][22]30 are intrinsically biased towards highly annotated genes, and limited functional cues can be deduced from the trapped sequences representing ESTs or new genes. With the gene-trap array, virtually any cell type can now be screened for differentially expressed genes.…”
Section: Discussionmentioning
confidence: 99%
“…Mice carrying a gene-trap insertion in the Neo1 gene have been constructed as described previously (Leighton et al, 2001;Mitchell et al, 2001), and homozygous mutants were reported to display perinatal lethality (Srinivasan et al, 2003), but this allele is not well characterized. We refer to the allele here as Neo1 Gt(KST265)Byg (abbreviated Neo1 Gt ).…”
Section: The Neo1 Gt Allele Is Hypomorphic and Results In Incompletelmentioning
confidence: 99%
“…Mice carrying a secretory gene-trap vector insertion into intron 7 of the Neo1 gene were constructed previously (Leighton et al, 2001;Mitchell et al, 2001). The embryonic stem (ES) cell line that carried the secretory gene trap from which this mouse line was developed was designated KST265, and we therefore refer to the allele as Neo1 Gt(KST265)Byg (abbreviated Neo1 Gt ).…”
Section: Micementioning
confidence: 99%
See 1 more Smart Citation